Shadow Pricing, Information, and Stability in a Simple Open Economy - Warr, Peter G. (Quarterly Journal of Economics, 1978)
I. Introduction, 95. — II. Notation and assumptions, 96. — III. Necessary conditions for a second-best optimum, 98. — IV. Informational requirements, 100. — V. Stability, 103. — VI. Some alternative solutions, 109. — VII. Summary and conclusions, 112. — Appendix A: Proof of Proposition 1,113. — Appendix B: Proof of Proposition 3,115.